Evaluating the Utilization of the National Cancer Institute Computed Tomography Program for Calculating Size-specific Dose Estimate and Effective Dose in Computed Tomography in Thai Pediatric Patients - Supawitoo Sookpeng; Colin J. Martin; Natch Rattanarungruangchai; M. Rosario López-Gonzalez (Journal of Medical Physics)
The objectives of this study were to assess the feasibility of utilizing computational calculations and the simulation of the National Cancer Institute computed tomography (NCICT) dosimetry system to obtain size-specific dose estimate (SSDE) and effective dose values resulting from the most common CT examinations in Thai pediatric patients and to evaluate age- and size-specific k conversion factor. For the calculation methods, SSDEs were calculated using the American Association of Physicists in Medicine Report No. 220 and 293 methodologies. The results revealed that SSDEs derived from CT scans of the body, obtained through the two different methods, varied by within 10%. The size of the patient and the scanning distance had an impact on the variability of E values derived from NCICT. Age- and size-specific k conversion factors may be used as a first line to estimate risk for the pediatric patients.